2001
DOI: 10.1051/forest:2001141
|View full text |Cite
|
Sign up to set email alerts
|

The above- and belowground carbon pools of two mixed deciduous forest stands located in East-Flanders (Belgium)

Abstract: -Carbon (C) storage was studied in both an oak-beech and an ash stand located in the 80-year-old Aelmoeseneie experimental forest (Gontrode, East-Flanders, Belgium). The total carbon stock amounted to 324.8 tons C ha -1 in the oak-beech stand and 321.4 tons C ha -1 in the ash stand. In the oak-beech stand 41.5% of the total C was found in the soil organic matter, 11% in the litter layer and 47.5% in the vegetation. In the ash stand, the soil organic matter contained 53.0% of the total C stock, the litter layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 30 publications
1
12
0
2
Order By: Relevance
“…Hence, in some of the sites included in this study it is easily possible that belowground C storage, including that in soil and roots, may be more important than aboveground C storage. This agree with findings of Walle et al (2001) and Jia and Akiyama (2005) who found more C below then above ground in some mature forest ecosystems. The average content of C in soil of 30 years old temperate forests varies widely around 134 t ha -1 (Brady and Weil 2002).…”
Section: Discussionsupporting
confidence: 94%
“…Hence, in some of the sites included in this study it is easily possible that belowground C storage, including that in soil and roots, may be more important than aboveground C storage. This agree with findings of Walle et al (2001) and Jia and Akiyama (2005) who found more C below then above ground in some mature forest ecosystems. The average content of C in soil of 30 years old temperate forests varies widely around 134 t ha -1 (Brady and Weil 2002).…”
Section: Discussionsupporting
confidence: 94%
“…Forest floor carbon represented 12.4% of the total C fixed in the pine ecosystem analyzed, while it represented the 7.3% of the total carbon fixed (5.4 Mg C ha -1 ) in the oak stands. Although higher proportions were found in mixed forest of oak and beech in Belgium areas by Vande Walle et al (2001), smaller values were found by previous researchers such as Gallardo & González (2004) or Ordóñez et al (2008).…”
Section: Species Forest Compositionmentioning
confidence: 41%
“…The smaller C/N ratio reflects that the forest floor degradation in oak is faster than the pine because micro-organisms prefer digestion of litter with a low C/N ratio (< 20) to satisfy their nitrogen needs (Vande Walle et al, 2001). Previous authors agreed as to the critical (tree biomass, dead wood, scrub, forest floor and soil) of the two types of forest ecosystems (pine and oak stands) was 110.7 Mg C ha -1 and 73.9 Mg C ha -1 , respectively (unpublished data).…”
Section: Species Forest Compositionmentioning
confidence: 99%
“…Так, оцінена наземна біомаса заповідного вікового листяного лісу в долині річки Тічино, Італія становила 348 т га -1 та відповідно 174 т га -1 вуглецю, з якої 63 % складає біомаса дуба звичайного [GRANATA et al, 2016]. Запас наземної біомаси 80-річного буково-дубового лісу наукового призначення в Бельгії становив 123 т га -1 , а накопиченого вуглецю -79 т га -1 [WALLE et al, 2001]. Визначена середня маса накопиченого вуглецю в стовбуровій деревині досліджених дубів парку «Феофанія» відповідає даним інших країн Європи.…”
Section: результати досліджень та їх обговоренняunclassified
“…Згідно нашої оцінки у 1992 році, коли середній вік досліджених дубів Феофанії був 42 роки, середня маса вуглецю становила 144 кг. У 80-річному буково-дубовому насадженні в Бельгії запас вуглецю в стовбуровій фракції дуба становив 41 т га -1 [WALLE et al, 2001], що в перерахунку на одне дерево складало 247 кг. У дослідженому нами деревостані такий рівень акумульованого вуглецю було досягнуто при середньому віці дерев 53 роки (рис.…”
Section: результати досліджень та їх обговоренняunclassified